Les figurines en terre cuite gallo-romaines - Bémont, Colette; Jeanlin, Micheline; Lahanier, Christian (Documents d'archéologie française, 1993)
For the first time since the publications of A. Blanchet at the beginning of the century, about fifty french and foreigners archaeologists have reviewed research on gallo-roman pipe-day figurines, produced in moulds and commercialised from the 1st to IIIrd centuries AD. Are studied here successively: the workshops, production techniques, coroplathes, iconographical inventories, chronology, the origins and use of the figurines, their distribution in and outside France. The results of physico-chemical analysis of clays which should in the future help in the identification of the principal workshops and an expert system applied to the identification of figurine fragments are finally presented. This considerable mass of informations will for many years be a reference base.